The Southernmost People of Greenland - Dialects and Memories (Vol. 337):Qavaat - Oqalunneri Eqqaamassaallu - Mâliâraq Vebæk (Monographs on Greenland | Meddelelser om Grønland, 2006)
During the mid-20th century, old South Greenlanders still spoke their genuine dialects when Mâliâraq Vebæk, herself a South Greenlander, born 1917, collected on tape stories and descriptions of pre-modern daily life from 42 informants. In this volume, the texts appear in dialectal transcription and translated into English, as well as in sound on the inserted CD-Rom, containing the tape recordings. Among the South Greenlandic dialects, the southernmost from the Cape Farewell region, which is now extinct, attracts particular interest, because this area received emigrants from the gradually depopulated southeast coast during the 19th century. The so-called qavak-dialect of the Cape Farewell region thus became an interesting mixture of the southeast and southwest Greenlandic dialects. This publication is targetted at linguists and is the first and only presentation of the South Greenlandic dialects. A phonological introduction is offered for the benefit of the linguists, but any reader of English (or the dialects) interested in stories, Greenland etc. can fully enjoy the texts.